2013
DOI: 10.1038/srep01332
|View full text |Cite
|
Sign up to set email alerts
|

Seabird diets provide early warning of sardine fishery declines in the Gulf of California

Abstract: Small pelagic fisheries show wide fluctuations, generally attributed to oceanographic anomalies. Most data on these fisheries come from landings, often reporting sustained catches-per-unit-effort (CPUEs) until a decline occurs. Fishery-independent data are important as management tools. In this study we show that the proportions of Pacific Sardine and Northern Anchovy in the diet of three seabird species (California Brown Pelicans, Heermann's Gulls, and Elegant Terns) nesting in spring in the Gulf of Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 18 publications
(30 reference statements)
1
38
0
1
Order By: Relevance
“…The fact that studies on 5 additional species, aside from Heermann's Gull, show evidence of expansions during the late Pleistocene (100,000-30,000 yr BP) indicates that regional oceanographic change during that period affected multiple marine species in a similar manner. The results of Díaz-Viloria et al (2012) on the northern anchovy are most relevant to our results, given that long-term studies on the diet of Heermann's Gull have shown that northern anchovy is an important prey species (Velarde et al 1994(Velarde et al , 2013(Velarde et al , 2015a. The population expansion of northern anchovy (Díaz-Viloria et al 2012) could have been a key factor in the increased breeding success of Heermann's Gull and its own demographic expansion.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The fact that studies on 5 additional species, aside from Heermann's Gull, show evidence of expansions during the late Pleistocene (100,000-30,000 yr BP) indicates that regional oceanographic change during that period affected multiple marine species in a similar manner. The results of Díaz-Viloria et al (2012) on the northern anchovy are most relevant to our results, given that long-term studies on the diet of Heermann's Gull have shown that northern anchovy is an important prey species (Velarde et al 1994(Velarde et al , 2013(Velarde et al , 2015a. The population expansion of northern anchovy (Díaz-Viloria et al 2012) could have been a key factor in the increased breeding success of Heermann's Gull and its own demographic expansion.…”
Section: Discussionsupporting
confidence: 59%
“…The population-expansion interpretation is also supported by the highly significant negative value of Fu's F S , a more sensitive indicator than Tajima's D. Evidence from MDA and BSP indicates that Heermann's Gull experienced a demographic expansion between 100,000 and 45,000 yr BP, a period that roughly coincided with the end of the Pleistocene glacial maxima to the last glacial retreat. The signature of major population expansion during the late Pleistocene for Heermann's Gulls is likely related to large-scale ecological shifts in the North Pacific and Gulf of California due to historical climate change and the subsequent demographic expansions of associated marine species, including species that are presently important components in the diet of Heermann's Gulls, such as the northern anchovy (Engraulis mordax; Velarde et al 1994Velarde et al , 2013Velarde et al , 2015a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because life history attributes and behaviors vary (e.g., morphology, foraging habitat preference, diving ability), seabird species have differential sensitivities to variation in prey availability (Ainley et al 1995, Furness and Tasker 2000, Velarde et al 2013. Therefore, our overall goal is to understand spatially explicit oceanprey and seabird-prey relationships from the perspective of variation in life histories.…”
Section: Introductionmentioning
confidence: 99%